High-specific-energy 3D structure energy integrated device
By designing a high-specific energy 3D structure energy integrated device in drones, using metal anode grid and 3D printing technology, the problem of limited battery life and intelligence level of the drone is solved, and higher energy is achieved Density and mechanical properties.
Patent Information
- Application Number
- CN202411409258.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-11
AI Technical Summary
Due to the low battery energy density and low structural energy utilization, existing drones have limited battery life and intelligence levels.
A high-specific energy 3D structure energy integrated device is designed to increase the contact surface area between the anode and the electrolyte by gridding the metal anode and filling it with alkaline semisolid electrolytes, and to improve the compatibility between the electrode and the electrolyte with 3D printing technology.
It achieves faster reaction rates, higher power density and energy density, and improves the endurance and mechanical performance of the drone.
Smart Images

Figure CN119419419A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of structural energy storage integration, and in particular relates to a high specific energy 3D structural energy integration device. Background Art
[0002] Fully electric micro-UAV equipment provides important support for completing high-altitude operations, rapid cruise search and rescue, high-altitude reconnaissance and other tasks. It usually adopts a distributed energy design, that is, the energy system is distributed in different parts of the UAV equipment, thereby effectively improving the overall energy capacity of the UAV. At present, the main power source of UAVs is lithium-ion batteries, but the energy density of commercial lithium-ion batteries is difficult to exceed 450Wh / kg in the short term, which greatly restricts the cruising ability, working time and intelligence level of UAVs.
[0003] Metal-air battery is a battery that converts chemical energy into electrical energy through a redox reaction between metal and oxygen in the air. It has the advantages of stable performance and low price, and the energy density can reach 800Wh / kg. Metal-air battery mainly consists of three parts: metal electrode, alkaline electrolyte and air electrode. At present, the common metal-air battery is a flat structure formed by stacking metal electrodes, electrolytes (electrolyte + diaphragm) and air electrodes. There are problems such as low metal electrode utilization, small contact area between air electrode and air, and low battery space utilization. At the same time, traditional planar electrodes may produce longer ion transmission channels and smaller interface surface active areas, which may reduce electrochemical performance.
[0004] At present, drones generally use batteries as energy sources on their structural parts. This method reduces the range of drones because they are carrying the weight of both the structural parts and the batteries. Therefore, how to design a structure and energy integrated device for drones based on metal-air batteries, so that the metal anode has a larger specific surface area and more reaction area, while taking into account mechanical properties, so that drones based on this integrated device can have excellent endurance, has become a current research hotspot. Summary of the invention
[0005] In view of the problems existing in the background technology, the purpose of the present invention is to provide a high-energy-density 3D structural energy integrated device. The device uses the metal anode of the metal-air battery as the structural component of the drone, and at the same time grids the metal anode to increase the contact surface area between the metal anode and the electrolyte, thereby accelerating the reaction rate of the anode, and can achieve a shorter ion diffusion path, lower interface resistance and charge transfer resistance in a limited space; at the same time, the use of 3D printed semi-solid electrolytes improves the compatibility of the heterogeneous interface between the electrode and the electrolyte, thereby greatly improving the ion migration rate and the sustainable discharge capacity of the battery. Through the design of the device of the present invention, it has excellent mechanical properties while meeting the power supply needs of the drone, effectively solving the problem of the survivability of the drone.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A high-energy-density 3D structural energy integrated device, comprising a metal bracket, a metal grid arranged on the metal bracket and a metal air battery; the metal bracket comprises a cylindrical frame 1, a cantilever beam 2 fixedly connected to the wall of the cylindrical frame 1, and the other end of the cantilever beam 2 is fixedly connected to a connecting plate 3; wherein the cylindrical frame 1 is used to fix the power device of the UAV, and the connecting plate is used to be fixedly connected to the main fuselage of the UAV;
[0008] Metal grids are evenly arranged on the cylindrical frame and the cantilever beam, and alkaline semi-solid electrolyte is filled between two adjacent grids and around the grids, and then an air electrode layer, a breathable and water-blocking film and an insulating sealing layer are sequentially coated around the alkaline semi-solid electrolyte;
[0009] The metal anode, alkaline semi-solid electrolyte, air electrode layer, and breathable water-blocking membrane constitute a complete metal-air battery; a number of through holes are opened on the insulating sealing layer, and air enters the metal-air battery through the through holes and reacts with the air electrode layer to generate current.
[0010] Furthermore, the opening is covered with PI tape to ensure air isolation. When in use, it is removed and used normally. When not in use, the opening is continued to be covered with PI tape. This method prolongs the battery life.
[0011] Furthermore, the grid structure, alkaline semi-solid electrolyte, breathable and water-blocking membrane and insulating sealing layer are all prepared by 3D printing.
[0012] Furthermore, the metal anode material is zinc or aluminum.
[0013] Furthermore, the air electrode layer is obtained by attaching a catalyst to a cathode current collector, the cathode current collector is nickel foam or copper foil, and the catalyst is Pt@C; the air-permeable and water-blocking membrane is polyurethane (PU), polydimethylsiloxane (PDMS), polytetrafluoroethylene (PTFE), etc.; the insulating sealing layer is polypropylene.
[0014] Furthermore, the 3D printing slurry of the alkaline semi-solid electrolyte includes polycaprolactone (PCL), dimethyl carbonate (DMC), KOH and ionized water.
[0015] Furthermore, the cylindrical bracket is not the main load-bearing structure, and the load condition does not need to be considered. Therefore, the bracket is regarded as a single cantilever with one end fixed and the other end hanging the load. According to the deflection formula:
[0016]
[0017] Where f is the deflection, P is the stress, l is the length of the cantilever beam, E is the Young's modulus of the cantilever beam material, and I is the moment of inertia of the cantilever beam section;
[0018] The formula for calculating the moment of inertia of a rectangular section is,
[0019]
[0020] Where a is the width of the cantilever beam section, and b is the height of the cantilever beam section;
[0021] Combining formulas (1) and (2), and based on the structural mechanics of the UAV bracket, it can be seen that the cantilever beam deflection must be greater than 0.1.
[0022] a 3 bE>6.4×10 -6 (3)
[0023] Based on formula (3), once the material of the bracket is determined, the size of the cantilever beam can be determined based on the Young's modulus of the material.
[0024] The present invention also provides a UAV, which includes a main body, a structural energy integration device and a power device;
[0025] The power device includes a motor and a propeller electrically connected to the motor; wherein the structural energy integration device is symmetrically and fixedly arranged on the main body, the motor is fixedly arranged in a cylindrical frame of the structural energy integration device, and a control unit is arranged on the main body for controlling the output of the electrode, thereby controlling the flight of the UAV.
[0026] Furthermore, the UAV is a quad-rotor UAV or a two-rotor UAV.
[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0028] 1. Compared with conventional air batteries of the same volume, the metal-air battery described in the present invention is a structural energy integrated device. The metal anode is gridded and an alkaline semi-solid electrolyte is filled between the grids, so that the metal anode and the electrolyte have a higher contact area and specific surface area, a higher volume utilization rate, and a higher proportion of active substances, thereby giving the air structure battery a faster reaction rate, higher power density and energy density.
[0029] 2. The larger specific surface area between the air electrode and the metal anode is conducive to the uniform diffusion, reduction and transfer of oxygen, promoting OH - Diffusion and reaction on the metal anode and air electrode sides improve the power density of the battery.
[0030] 3. The main structure of the present invention is prepared by 3D printing technology, which has micron-level manufacturing control capabilities, can realize the preparation of micron-level ultra-thin dielectric films and composite electrode layers, improve electrode accuracy, and provide an effective structural basis for solid-state or semi-solid-state battery interface optimization. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the structure of the bracket and metal grid in the high specific energy 3D structure energy integration device of the present invention.
[0032] Figure 2 It is a partial cross-sectional view of the high specific energy 3D structure energy integrated device of the present invention.
[0033] Figure 3 It is a dimensional parameter diagram of a local cross-section of the high specific energy 3D structure energy integration device of the present invention. DETAILED DESCRIPTION
[0034] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the implementation modes and the accompanying drawings.
[0035] A high specific energy 3D structural energy integrated device comprises a metal support, a metal grid arranged on the metal support and a metal air battery; the structural schematic diagram of the metal support and the metal grid is as shown in Figure 1 As shown, the metal bracket includes a cylindrical frame 1, a cantilever beam 2 fixedly connected to the wall of the cylindrical frame 1, and the other end of the cantilever beam 2 is fixedly connected to a connecting plate 3; wherein the cylindrical frame 1 is used to fix the power device of the UAV, and the connecting plate is used to be fixedly connected to the main fuselage of the UAV;
[0036] Metal grids are arranged on both the cylindrical frame and the cantilever beam, wherein the metal grids on the cylindrical frame are evenly arranged on the circumference along the height direction of the cylindrical frame, and the length is the same as the height of the cylindrical frame; the metal grids on the cantilever beam are evenly arranged along the width direction of the cantilever beam, and the length is the same as the length of the cantilever beam;
[0037] The partial cross-section of the cantilever beam device is shown in Figure 2 As shown, an alkaline semi-solid electrolyte is filled between two adjacent grids and around the grids, and then an air electrode layer, a breathable and water-blocking membrane, and an insulating sealing layer are sequentially coated around the alkaline semi-solid electrolyte;
[0038] The metal anode, alkaline semi-solid electrolyte, air electrode layer, and breathable water-blocking membrane constitute a complete metal-air battery; a number of through holes are opened on the insulating sealing layer, and air enters the metal-air battery through the through holes and reacts with the air electrode layer to generate current.
[0039] Figure 3 The dimensional parameter diagram of the local cross section of the high specific energy 3D structure energy integration device of the present invention. The bracket is regarded as a single cantilever with one end fixed and the other end hanging the load. According to the deflection formula:
[0040]
[0041] Where f is the deflection, P is the stress, l is the length of the cantilever beam, E is the Young's modulus of the cantilever beam material, and I is the moment of inertia of the cantilever beam section;
[0042] The formula for calculating the moment of inertia of a rectangular section is,
[0043]
[0044] Where a is the width of the cantilever beam section, b is the height of the cantilever beam section; d is the half length of the grid, and h is the thickness of the grid. Combining formulas (1) and (2), and based on the fact that the deflection of the cantilever beam of the drone does not exceed 0.1, we can obtain:
[0045] a 3 bE>6.4×10 -6 (3)
[0046] Based on formula (3), once the material of the bracket is determined, the size of the cantilever beam can be determined based on the Young's modulus of the material.
[0047] Example 1
[0048] The required metal bracket, including the metal grid, was processed by CNC machine tools. The overall bracket was 2 mm wide and 7 mm high, of which the width of the metal bracket excluding the grids on both sides was 0.5 mm. Similarly, the metal grid was prepared by cutting the cylindrical frame and the cantilever beam surface by machine tools. The grid thickness was 50 μm and the depth was 0.75 mm. KOH gel was printed in the gaps between the metal grids by 3D printing, and the thickness was controlled to be 10 μm.
[0049] The 3D printing preparation process of KOH gel is as follows:
[0050] Step 1. Prepare 3D printing slurry: add an appropriate amount of dimethyl carbonate (DMC) to a 25 ml beaker, heat it to 60 ° C, then add polycaprolactone (PCL) to dimethyl carbonate (DMC), stir, then add KOH and deionized water, set the stirring speed to 450 r / min, stir for 1.5 hours, and you can get 3D printing slurry;
[0051] Step 2. Perform 3D printing: load the 3D printing slurry into the syringe, install the needle after exhausting the gas, adjust the syringe height and gas pressure, and use the 3D printer to print the 3D printing slurry between the grids to obtain a 3D printed semi-solid electrolyte.
[0052] The air electrode layer uses Pt / C as a catalyst and nickel foam or copper foil as the cathode current collector.
[0053] A PU breathable and water-blocking layer is constructed on the surface of the air electrode layer, the main component of which is polyurethane. High-performance polyurethane is synthesized using isophorone diisocyanate (IPDI), hydroxyethyl methacrylate (HEMA), and polytetramethylene ether glycol (PTMEG) as raw materials to obtain 3D printing polyurethane material; the material is added to the hopper of a twin-screw extruder, extruded, pulled, pelletized and dried by a pelletizer under the conditions of a twin-screw extruder temperature of 190℃-210℃ and a rotation speed of 80r / min, and the dried pellets are introduced into a single-screw extruder, and after extrusion, they are pulled by a tractor and water-cooled to be processed into wire that meets the needs of a 3D printer, and the material is coated on the surface of the air electrode layer using a 3D printer.
[0054] Polypropylene, toughening agent, inorganic filler, antioxidant, coupling agent and other additives are mixed evenly in a high-speed mixer, the mixed raw materials are added into a twin-screw extruder, cooled and granulated after melt extrusion, the particles are dried and then injection molded on an injection molding machine to prepare samples, the temperature of the 3D printer is adjusted, and a polypropylene insulating layer is prepared on the surface of the PU breathable and water-blocking layer.
[0055] Combining the specific energy formula and Figure 1 The structural design diagram is shown. The mass ratio / volume specific energy of the battery is calculated, as shown in Table 1.
[0056] Table 1 Battery component parameters
[0057]
[0058] Example 2
[0059] The difference between this embodiment and embodiment 1 is that the thickness of the zinc grid is different. The thickness of each layer of zinc metal grid in this embodiment is 100 μm, and other parameters are the same as those in embodiment 1.
[0060] Comparative Example 1
[0061] The only difference between this comparative example and Example 1 is that there is no air-permeable and water-blocking layer, and the other structures and parameters are the same as those of Example 1.
[0062] Comparative Example 2
[0063] The difference between this comparative example and Example 1 is that the electrolyte, supramolecular membrane and insulating shell are not 3D printed, but are made into a gel electrolyte membrane, a water-blocking and breathable supramolecular membrane and a snap-on insulating shell in a conventional manner, and assembled by pasting.
[0064] Comparative Example 3
[0065] The difference from Example 1 is that the device does not use a grid-shaped metal bracket design and a 3D printing method, and the battery is manufactured by a conventional method.
[0066] Performance Testing:
[0067] Electrochemical performance tests were conducted on each embodiment and comparative example, and LSV tests were conducted between 1.6V and 0.2V to ensure that the 3D structure energy integrated device can discharge and meet the actual application conditions. At the same time, the discharge voltage and discharge time of the zinc metal air battery were tested at a constant current of 10mA, and the corresponding battery capacity and specific energy were calculated. The specific performance comparison is shown in Table 2.
[0068] The calculation formula is:
[0069] Battery mass specific energy = battery capacity (mAh) / mass (g) (4)
[0070] Actual reaction zinc mass = battery capacity (mAh) / zinc energy density (mAh / g) (5)
[0071] Table 2 Calculation of battery mass ratio / volume ratio energy
[0072]
[0073] It can be seen from Table 2 that the use of the structural energy integration device of the present invention can improve the energy density of the load, thereby extending the use time.
[0074] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.
Claims
1. A high specific energy 3D structure energy integrated device, characterized in that: It includes a metal bracket, a metal grid arranged on the metal bracket and a metal air battery; the metal bracket includes a cylindrical frame, a cantilever beam fixedly connected to the cylindrical frame wall, and the other end of the cantilever beam is fixedly connected to a connecting plate; wherein the cylindrical frame is used to fix the power device of the UAV, and the connecting plate is used to be fixedly connected to the main fuselage of the UAV; Metal grids are evenly arranged on the cylindrical frame and the cantilever beam, and alkaline semi-solid electrolyte is filled between two adjacent grids and around the grids, and then an air electrode layer, a breathable and water-blocking film and an insulating sealing layer are sequentially coated around the alkaline semi-solid electrolyte; The metal anode, alkaline semi-solid electrolyte, air electrode layer, and breathable water-blocking membrane constitute a complete metal-air battery; a number of through holes are opened on the insulating sealing layer, and air enters the metal-air battery through the through holes and reacts with the air electrode layer to generate current.
2. The high specific energy 3D structure energy integrated device according to claim 1, characterized in that: Cover the opening with PI tape to ensure air isolation. When in use, remove it and use it normally. When not in use, continue to cover the opening with PI tape. This method can extend the battery life.
3. The high specific energy 3D structure energy integrated device according to claim 1, characterized in that: Alkaline semi-solid electrolyte, breathable and water-blocking membrane and insulating sealing layer are all prepared by 3D printing.
4. The high specific energy 3D structure energy integrated device according to claim 1, characterized in that: The metal anode material is zinc or aluminum.
5. The high specific energy 3D structure energy integrated device according to claim 1, characterized in that: The air electrode layer is obtained by attaching a catalyst to a cathode current collector, the cathode current collector is nickel foam or copper foil, and the catalyst is Pt@C; the air-permeable and water-blocking membrane is polyurethane, polydimethylsiloxane or polytetrafluoroethylene; and the insulating sealing layer is polypropylene.
6. The high specific energy 3D structure energy integrated device according to claim 1, characterized in that: The 3D printing slurry of the alkaline semi-solid electrolyte includes polycaprolactone, dimethyl carbonate, KOH and deionized water.
7. The high specific energy 3D structure energy integrated device according to claim 1, characterized in that: The cylindrical bracket is not the main load-bearing structure, and the load condition does not need to be considered. Therefore, the bracket is regarded as a single cantilever with one end fixed and the other end hanging the load. According to the deflection formula: Where f is the deflection, P is the stress, l is the length of the cantilever beam, E is the Young's modulus of the cantilever beam material, and I is the moment of inertia of the cantilever beam section; The formula for calculating the moment of inertia of a rectangular section is, Where a is the width of the cantilever beam section, and b is the height of the cantilever beam section; Combining formulas (1) and (2), and based on the structural mechanics of the UAV support, it can be seen that the cantilever beam deflection must exceed 0.1; a 3 bE>6.4×10 -6 (3) Based on formula (3), once the material of the bracket is determined, the size of the cantilever beam can be determined based on the Young's modulus of the material.
8. A drone, characterized in that: The drone comprises a main body, a high specific energy 3D structural energy integrated device as claimed in any one of claims 1 to 7, and a power device; The power device includes a motor and a propeller electrically connected to the motor; wherein, the high-energy-density 3D structural energy integration device is symmetrically and fixedly arranged on the main body, the motor is fixedly arranged in a cylindrical frame of the high-energy-density 3D structural energy integration device, and a control unit is arranged on the main body to control the output of the electrode, thereby controlling the flight of the UAV.
9. The drone according to claim 8, characterized in that: The UAV is a quad-rotor UAV or a bi-rotor UAV.